Generation of stable colloidal gold nanoparticles by ultrashort laser-induced melting and fragmentation - Vasa, Parinda; Sharma, Rahul; Singh, Mamraj; Dharmadhikari, Aditya K; Dharmadhikari, Jayashree A; Mathur, Deepak (Materials research express, 2014)
We report on generation of stable colloidal gold nanoparticles by ultrashort laser-induced melting and fragmentation. Irradiation of colloidal gold nanoparticles (of initial size larger than 25 nm) by 56 fs long, near-IR pulses of moderate fluence (1.3-5.3 J cm−2) generates very small (2.5 nm) nanoparticles with a narrow size distribution (±0.5 nm). Systematic measurements show the final size of fragmented nanoparticles to be (i) very weakly dependent on the original size and particle shape as well as of pump laser wavelength (800 nm, 1200 nm and 1350 nm), but (ii) strongly dependent on laser parameters; moreover, fragmentation is effectively controllable by pulse fluence and irradiation time. The fragmented particles appear to be contaminant free and have high crystalline quality. We find that the fragmented particles are stable over a time period of more than three months. Stable, contaminant-free, crystalline colloidal gold nanoparticles of sizes around 3 nm, with very narrow size distribution, have potential utility in diverse nanotechnological applications, ranging from biologically relevant imaging to nanoscopic generators of high-frequency mechanical vibrations in the GHz range.